Evaluation of the Human Pulmonary Activation-Regulated Chemokine (CCL18/PARC) and Alkaline Phosphatase (ALP) Levels in Iraqi Patients with Rheumatoid Arthritis - Al-Hashimi, Nawal Haider; Al-Gebori, Abdulnasser M.; Alosami, Mohammed Hadi Munshed (Iraqi Journal of Science, 2020)
Rheumatoid arthritis (RA) is one of the chronic inflammatory autoimmune diseases which occurs as a result of unknown reasons. This study was conducted at Baghdad Teaching Hospital/City of Medicine, where blood samples were taken from 60 Iraqi patients with RA (49 females and 11 males) and these patients were matched by age and sex with 20 healthy controls (16 females and 4 males). Patients with RA were diagnosed by a consultant rheumatologist according to ACR / EULAR criteria in 2010. In this study the patients were divided into four groups as follows; the first group consisted of 12 patients treated with methotrexate (MTX), the second group consisted of 10 patients treated with etanercept, the third group consisted of 18 patients treated with a combination of MTX, etanercept and prednisolone, the fourth group consisted of 20 patients treated with MTX and etanercept. Enzyme linked immunosorbent assay (ELISA) was used to detect CCL18/PARC antibodies, while a spectrophotometer (Humalyzer2000) was used for the measurement of alkaline phosphatase (ALP). Serum levels of CCL18 / PARC showed a significant increase in RA patients compared with healthy controls (p â‰¤ 0.001). The levels of CCL18/PARC showed a significant correlation with disease activity (CDAI), except in RA patients treated with etanercept. There was also no significant correlation between CCL18/PARC and erythrocyte sedimentation rate (ESR). The results showed a significant increase in serum levels of alkaline phosphatase (ALP) was recorded in RA patients (with treatment) as compared to healthy controls (p â‰¤ 0.001).